Myocardial Tissue Reverse Remodeling After Guideline-Directed Medical Therapy in Idiopathic Dilated Cardiomyopathy. (January 2021) - Xu, Yuanwei; Li, Weihao; Wan, Ke; Liang, Yaodan; Jiang, Xincheng; Wang, Jie; Mui, David; Li, Yangjie; Tang, Siqi; Guo, Jiajun; Guo, Xinli; Liu, Xiumin; et al.
Abstract : Background: The prognosis of patients with idiopathic dilated cardiomyopathy (DCM) has improved remarkably in recent decades with guideline-directed medical therapy. Left ventricular (LV) reverse remodeling (LVRR) is one of the major therapeutic goals. Whether myocardial fibrosis or inflammation would reverse associated with LVRR remains unknown. Methods: A total of 157 prospectively enrolled patients with DCM underwent baseline and follow-up cardiovascular magnetic resonance examinations with a median interval of 13.7 months (interquartile range, 12.2–18.5 months). LVRR was defined as an absolute increase in LV ejection fraction of >10% to the final value of ≥35% and a relative decrease in LV end-diastolic volume of >10%. Statistical analyses were performed using paired t test and student t test, logistic regression analysis, and linear regression analysis. Results: Forty-eight (31%) patients reached LVRR. At baseline, younger age, worse New York Heart Association class, new-onset heart failure, lower LV ejection fraction, absence of late gadolinium enhancement, lower myocardial T2, and extracellular volume were significant predictors of LVRR. During the follow-up, patients with and without LVRR both showed a significant decrease of myocardial native T1 (LVRR: [baseline] 1303.0±43.6 ms; [follow-up] 1244.7±51.8 ms; without LVRR: [baseline] 1308.5±80.5 ms; [follow-up] 1287.6±74.9 ms, both P <0.001), matrix and cellular volumes while no significant difference was observed in T2 or extracellular volume values after treatment. Conclusions: In patients with idiopathic DCM, the absence of late gadolinium enhancement, lower T2, and extracellular volume values at baseline are significant predictors of LVRR. The myocardial T1, matrix, and cell volume decrease significantly in patients with LVRR after guideline-directed medical therapy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: ChiCTR1800017058. Abstract : Supplemental Digital Content is available in the text.